Research Productivity of Foot and Ankle Fellowship Faculty. Issue 1 (February 2022) - Sherman, Nathan; Bridge, Nathaniel; Khwaja, Ansab; Du, Peter; Truchan, Lisa
Background: Contribution to literature is critical for progress in the field of orthopaedics. No previous study has yet examined the academic productivity of foot and ankle surgery fellowship faculty. Purpose: To evaluate the publishing productivity of foot and ankle fellowship faculty. Methods: Faculty and program characteristics of orthopaedic foot and ankle fellowship programs across the United States and Canada were collected from American Orthopaedic Foot and Ankle Society (AOFAS) and program websites. Faculty publication productivity measures, including publications, number of publications in specific journals, number of citations, and Hirsch index (h-index) were gathered using the Scopus database. Results: A total of 48 AOFAS foot and ankle surgery fellowship programs were identified with an associated 185 faculty members. The mean number of publications per faculty member was 44.9 (SD = 53.0; range = 0-323), with a mean h-index of 11.9 (SD = 10.6; range = 0-54). A total of 144 (77.8%) academic-affiliated faculty had a significantly greater number of publications ( P < .01), total citations ( P < .05), and publications in Foot and Ankle International ( P < .05), Journal of Bone and Joint Surgery ( P < .05), Clinical Orthopaedics and Related Research ( P < .05), and Journal of the American Academy of Orthopaedic Surgeons ( P < .05) compared to the 41 (22.2%) nonacademic faculty. There were no significant differences between measures of publication productivity between male and female faculty, except for maximum citations in a single article (67.1 vs 142.3; P < .05). Conclusions: Academic-affiliated foot and ankle fellowship faculty have higher research productivity than nonacademic surgeons. The mean h-index of foot and ankle fellowship faculty was 11.9, which is lower than that reported in sports, joints, and spine fellowship faculty but higher than that reported for hand fellowship faculty. Level of Evidence: Level IV